Using Traceability to Mitigate Cognitive Biases in Software Development. - MOHAN, KANNAN; JAIN, RADHIKA (Communications of the ACM, 2008)
The article discusses the potential for cognitive bias to appear in the development of computer software, examining the use of traceability to eradicate the effect of cognitive bias while individuals perform change to design artifacts. Software developers may employ heuristics that are informed by cognitive biases when changing software artifacts, the article states. Other topics include the use of the cognitive aid traceability, simplifying complex inference tasks, the use of anchoring and adjustment, and peoples' initial estimates about a problem.